2018
DOI: 10.1111/famp.12406
|View full text |Cite
|
Sign up to set email alerts
|

When the “U” is not Inverted: Trajectories of Expressed Emotional Arousal Predict Relationship Satisfaction

Abstract: Maladaptive emotional reactivity and dysfunctional communication during couple conflict are both destructive to couple functioning, and observational research has elucidated how conflict escalates. However, much of the evidence is based on measures that combine content (i.e., what was said) and the emotion with which it was said, which are then examined using sequential analyses. Despite the general presumptions about underlying emotional reactivity and escalation in negative emotions as part of relationship d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 34 publications
1
16
1
Order By: Relevance
“…Thus, in the context of women expressing negative emotions, men may experience greater regulation as a positive experience and feel more satisfied in the relationship. Moreover, Fischer et al (2019) found that husbands were more satisfied if the couples’ overall emotional arousal decreased more sharply across the conversation, suggesting that husbands might be happier if the overall emotional tone of the conversation becomes progressively calmer. Thus, while the current findings should be considered preliminary, these findings are consistent with prior work suggesting that partners may experience the expression of more intense emotions from the other partner within a conversation as problematic, especially considering men’s response to emotions that come from women.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, in the context of women expressing negative emotions, men may experience greater regulation as a positive experience and feel more satisfied in the relationship. Moreover, Fischer et al (2019) found that husbands were more satisfied if the couples’ overall emotional arousal decreased more sharply across the conversation, suggesting that husbands might be happier if the overall emotional tone of the conversation becomes progressively calmer. Thus, while the current findings should be considered preliminary, these findings are consistent with prior work suggesting that partners may experience the expression of more intense emotions from the other partner within a conversation as problematic, especially considering men’s response to emotions that come from women.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the findings suggest that lessened escalation in emotional arousal occurred with concomitant improvements in relationship quality over the course of treatment (Christensen et al, 2004). Additionally, in a sample of nondistressed couples planning to marry, Fischer et al (2019) found that a steeper decline in vocal emotional arousal early in the conversation predicted greater relationship satisfaction over 3.5 years. These studies demonstrate that the overall trajectory (e.g., escalation) of vocal emotion across the conversation provides useful information about relationship quality over time.…”
mentioning
confidence: 99%
See 3 more Smart Citations